Accelerometer-measured sedentary behaviour and physical activity of inpatients with severe mental illness. (August 2017) - Kruisdijk, Frank; Deenik, Jeroen; Tenback, Diederik; Tak, Erwin; Beekman, Aart-Jan; van Harten, Peter; Hopman-Rock, Marijke; Hendriksen, Ingrid
Abstract: Sedentary behaviour and lack of physical activity threatens health. Research concerning these behaviours of inpatients with severe mental illness is limited but urgently needed to reveal prevalence and magnitude. In total, 184 inpatients (men n =108, women n =76, mean age 57, 4, 20% first generation antipsychotics, 40% second generation antipsychotics, 43% antidepressants, mean years hospitalisation 13 years), with severe mental illness of a Dutch psychiatric hospital wore an accelerometer for five days to objectively measure total activity counts per hour and percentages in sedentary behaviour, light intensity physical activity and moderate to vigorous physical activity. Accelerometer data were compared with data of 54 healthy ward employees. Patients showed significantly less activity counts per hour compared to employees (p=0.02), although the differences were small (d=0.32). Patients were sedentary during 84% of the wear time (50 min/h), spend 10% in light intensity physical activity and 6% in moderate to vigorous physical activity. Age was the only significant predictor, predicting less total activity counts/h in higher ages. Decreasing sedentary behaviour and improving physical activity in this population should be a high priority in clinical practice. Highlights: One of the first large-scale accelerometry studies in severe psychiatric inpatients. Inpatients with severe mental illness are impressively sedentary. Inpatients with severe mental illness are less active than a healthy comparison group. Interventions should focus primarily on increasing light to moderate physical activity.